INNOVATION IN TEACHING THE CULTURE OF VERBAL COMMUNICATION IN COMPETENCY-BASED PROFESSIONAL EDUCATION - Olga М. Osiyanova (Russian State Vocational Pedagogical University, 2015)
The aim of the investigation is to study the possibilities of the innovation system of teaching students verbal communication culture in a competency-based educational paradigm. Methods. The methods involve theoretical (the analysis of Russian and foreign research, modeling, projecting); empirical (observation, interview, questioning, diagnosing); pedagogical experiment; methods of mathematical statistics. Results. There has been developed an integrated model of innovation subject-oriented system which serves as the foundation for the project of students' linguistic education modernization by means of verbal communication culture. Scientific novelty. A scientific and socially important problem of modeling and theoretical justification of the integral verbal communication culture teaching system which concretizes theoretical and practical regulations of verbal communication culture teaching in the context of personal and professional students' development in the educational process has been solved; a new scientific result in the elaboration of a systemic-subject-oriented approach which serves as a basis for the innovation system and ensures systematic verbal communication culture teaching using reference points as a mechanism for «reflexive management» of person-to-person interaction has been achieved. Practical significance. The use of empirical data in educational practice contributes to ensuring a high level of verbal communication culture due to the content and didactic support of subject-oriented verbal communication culture teaching system encouraging communicative competence perfection of graduates.